Parameters of Poverty Alleviation Through Efficient Modern Energy Utilization in Nigeria - Abubakar, Yusuf Wara (IGI Global, 2023)
Efficient energy utilization should contribute to poverty alleviation in developing countries. A society that successfully shifted from non-modern sources of energy consumption to modern ones is said to witness more significant development. In developing countries such as Nigeria, inefficient modern energy use is connected with the high poverty level among the populace. Targeting assistance to improve modern energy utilization in society that directly affects people experiencing poverty might enhance a healthy society, improve the physical environment, and increase production in society. This research tends to establish the nexus between three parameters: modern energy efficiency health improvement wealth, modern energy efficiency environmental protection wealth, and the modern energy efficiency increased production wealth, relationships. The research will test the hypothesis that the higher the modern energy utilization, the lower the poverty in society. It will also respond to the question of how efficient modern energy utilization can alleviate poverty in society.
Keywords: 8. Economic growth; 11. Sustainability; 1. No poverty; 7. Clean energy